Buddhism : introducing the Buddhist experience - Mitchell, Donald W. (Donald William), 1943- (New York, Oxford University Press, 2002)
This book focuses on the depth of Buddhist experience as expressed in the teachings and practices of a wide array of its religious and philosophical traditions. Taking a broad and inclusive approach, this work spans over 2,500 years, featuring chapters on Buddhism's origins in India; Theravada and Mahayana Buddhism; and Buddhism in Southeast Asia, Tibet, China, Korea, and Japan. It also includes an extensive discussion of modern, socially engaged Buddhism and a concluding chapter on the spread of Buddhism to the West. Mitchell provides substantial selections of primary text material throughout that illustrate a great variety of moral, psychological, meditative, and spiritual Buddhist experiences. Buddhism features twenty-two boxed personal narratives provided by respected Buddhist leaders and scholars from around the world, including His Holiness the Dalai Lama, Dharma Master Sheng Yen, Dharma Master Cheng Yen, Jeffrey Hopkins, Sulak Sivaraksa, Rita M. Gross, Chatsumarn Kabilsingh, and Robert Aitken. These concise and intriguing essays give students a glimpse into what the topics discussed in the book actually mean in terms of human experience today. Ideal for courses in Buddhism, Asian religions, and Asian philosophy, Buddhism also incorporates helpful maps, numerous illustrations, a glossary, and suggestions for further reading
1. The life of Gautama Buddha -- 2. The teachings of the Buddha -- 3. The way of the elders -- 4. The great vehicle -- 5. The Indian experience of Buddhism -- 6. The Tibetan experience of Buddhism -- 7. The Chinese experience of Buddhism -- 8. The Korean experience of Buddhism -- 9. The Japanese experience of Buddhism -- 10. Modern Buddhism in Asia -- 11. Buddhism in the West
Includes bibliographical references and index
Keywords: Buddhism -- History; Buddhism -- history; History